Molecular analysis of an IS200 insertion in the gpt gene of Salmonella typhimurium LT2. - O'Reilly, C (1990)
A strain of Salmonella typimurium LT2 has been isolated which carries an insertion of approximately 700 bp in the gpt gene. The insertion in the gpt gene was shown to be the Salmonella-specific element IS200. The mutation in strain CR1 arose without selection during storage and is only the second phenotypically identified mutation caused by the insertion of IS200.